Possession and ownership - q; Dixon, Robert M. W. (Oxford : Oxford University Press, 2013)
Linguists and anthropologists explore the intriguing variety of possessive phrases denoting ownership of property, whole-part relations (such as body and plant parts), and blood and affinal kinship relations across a wide range of languages.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Possessives